Likeable business : why today's consumers demand more and how leaders can deliver - Kerpen, Dave. (New York : McGraw-Hill, 2013)
Lays out 11 strategies for organizations of all sizes to spur growth, profits, and overall success. This book helps any leader at a smallor mid-sized company increase profits and spur growth by applying the 11 principles of business likeability, such as: listening, authenticity, transparency, adaptability, simplicity, and gratefulness.
Includes index.
Includes bibliographical references and index.
Keywords: Management -- Social aspects; Customer relations; Social responsibility of business